Un Paisaje De Esperanza Y Progreso Configuración Urbana Mediante La Interacción De Los Componente Urbano Y Natural Del Municipio De Cisneros Antioquia (2022)
The urban configuration through the interaction of the urban and natural components is presented as the alternative of positive consolidation of two environments that are fragmented by physical barriers in the middle of the fabric. In the case of the municipality of Cisneros, thanks to the construction of the double carriageway of the road project (VINUS), the environmental problem and the landscape deterioration experienced in the sectors that border the Nus River and the road project became more noticeable,